Teaching Genomic Counseling: Preparing the Genetic Counseling Workforce for the Genomic Era - Hooker, Gillian W. (2014)
Genetic counselors have a long-standing history of working on the clinical forefront of implementing new genetic technology. Genomic sequencing is no exception. The rapid advancement of genomic sequencing technologies, including but not limited to next generation sequencing approaches, across all subspecialties of genetic counseling mandates attention to genetic counselor training at both the graduate and continuing education levels. The current era provides a tremendous opportunity for counselors to become actively involved in making genomics more accessible, engaging the population in decisions to undergo sequencing and effectively translating genomic information to promote health and well-being. In this commentary, we explore reasons why genomic sequencing warrants particular consideration and put forward strategies for training program curricula and continuing education programs to meet this need.